ANALYSIS OF PROFITABILITY AND ACTIVITY RATIO TO ASSESS FINANCIAL PERFORMANCE IN PT. ALUMINDO LIGHT METAL INDUSTRY TBK - Cantika; Putri Regina Rezki; Hesti Utami; Dinda Khairilia; Rezy Alvinri (Indragiri Research Center (ingreat), 2024)
This research aims to analyze the financial performance of PT Alumindo Light Metal Industry Tbk based on profitability and activity ratios during the 2022-2023 period. The main problem raised was the decline in financial performance which was marked by the company's consecutive net losses. This research uses a quantitative descriptive method with a time series approach. Data was obtained from company financial reports accessed via the official website of the Indonesia Stock Exchange. The analysis techniques used include activity and profitability ratio analysis to assess the effectiveness of asset management and the company's ability to generate profits. The research results show that the company's activity ratio has not shown optimal efficiency, while the profitability ratio is in the poor category. This indicates that the company's financial performance needs to be improved through efficiency strategies and better asset management.